Analisis Kualitatif Dampak Hukum Pidana Terhadap Masyarakat - Muhammad Ridwan Lubis (Dinasti Review Publisher, 2024)
It is the duty of the government to ensure the safety and order of the citizenry. Order and security are vital elements that shape a society that is psychologically healthy and prepared for global competition. This is because environmental factors strongly influence individual character. The Indonesian criminal justice system must be adequately enforced to realize this ideal. Nevertheless, there are occasions when the effectiveness of law enforcement is uncertain, resulting in a state of unrest among the public and the persistence of criminal activity. This study was therefore undertaken to ascertain the impact of implementing criminal legislation on enhancing community security and order. The methodology employed comprised a descriptive qualitative approach utilising interviews, observations and the distribution of questionnaires via the online platform Google forms. The findings indicated that the enforcement of criminal law has a constructive influence on the advancement of community security and order.